Fine mapping and identifying candidate gene of Y underlying yellow peel in Cucurbita pepo - Niu, Jianqing; Chen, Qiong; Lu, Xiaonan; Wang, Xueqiang; Tang, Zhongli; Liu, Qinghua; Lei, Fengjin; Xu, Xiaoyong (Frontiers in Plant Science, 2023)
As a conspicuous trait, peel color is one of the most important characteristics that affects commodity quality and consumer preferences. The locus Y underlying yellow peel in Cucurbita pepo (zucchini) was first reported in 1922; however, it’s molecular mechanism was still unknown. In this study, genetic analysis revealed that yellow peel was controlled by a single dominant genetic factor. Furthermore, Y was mapped in a ~170 kb region on chromosome 10 by Bulked Segregated Analysis (BSA) and fine mapping in F2 and BC1 segregating populations. The candidate region harbors fifteen annotated genes, among which Cp4.1LG10g11560 (CpCHLH) was regarded as a promising candidate gene. CpCHLH encodes a magnesium chelatase H subunit involved in chlorophyll biosynthesis, and its mutation can result in a reduction in chlorophyll content and yellow phenotype. Interestingly, a large fragment (~15 kb) duplication containing incomplete CpCHLH was inserted in the candidate interval resulting two reformed CpCHLH proteins in yellow parental line. It is most likely that the reformed CpCHLH proteins act as a malfunctional competitor of the normal CpCHLH protein to interrupt the formation of chlorophyll. Overall, the isolation of Y will shed light on the molecular mechanism of peel color regulation of zucchini and lay a foundation for breeding.